Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/pharmaceutics15030888
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Association of Carboxy-Terminal Dendrimers with Different Bound Numbers of Phenylalanine and Their Application to Drug Delivery

Abstract: T cells play important roles in various immune reactions, and their activation is necessary for cancer immunotherapy. Previously, we showed that polyamidoamine (PAMAM) dendrimers modified with 1,2-cyclohexanedicarboxylic acid (CHex) and phenylalanine (Phe) underwent effective uptake by various immune cells, including T cells and their subsets. In this study, we synthesized various carboxy-terminal dendrimers modified with different bound numbers of Phe and investigated the association of these dendrimers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Therefore [33]. In our previous report, we demonstrated that the Phe density at the dendrimer terminus affects the cellular interactions in PAMAM-CHex-Phe [29]. The most stable molecular structures of PAMAM-CHex-Phe, PAMAM-Ph-Phe, and PAMAM-C 6 -Phe, whose dendrimer contains four termini, were calculated and presented in Figure 4.…”
Section: Association Of Carboxy-terminal Phe-modified Dendrimers With...mentioning
confidence: 94%
“…Therefore [33]. In our previous report, we demonstrated that the Phe density at the dendrimer terminus affects the cellular interactions in PAMAM-CHex-Phe [29]. The most stable molecular structures of PAMAM-CHex-Phe, PAMAM-Ph-Phe, and PAMAM-C 6 -Phe, whose dendrimer contains four termini, were calculated and presented in Figure 4.…”
Section: Association Of Carboxy-terminal Phe-modified Dendrimers With...mentioning
confidence: 94%
“…Transfection: Jurkat cells were cultured in RPMI-1640 medium containing 10% FBS and a penicillin-streptomycin mixture. [13,14] Jurkat cells (1.0 × 10 5 cells per well) were seeded in a 24-well plate. Then, 50 μL of the solutions containing binary and ternary complexes (DNA 0.5 μg per well) was added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] A carboxy-terminal PAMAM dendrimer of G4 bearing both 1,2-cyclohexanedicarboxylic acid (CHex) and phenylalanine (Phe), named G4-CHex-Phe, is highly associated with immune cells, including spleen-and lymph nodederived T-cells and Jurkat cells. [12][13][14] Confocal microscopic analysis indicated that G4-CHex-Phe was internalized by T-cells, which is useful for drug delivery into T-cells. [13,14] In this study, we used G4-CHex-Phe to deliver pDNA into T-cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species bearing phenylalanine at more than half of the termini exhibited a higher association with T cells and other immune cells, with the highest affinity being reported to occur at 75% grafting. The robustness of the functionalized dendrimer as a drug vehicle was demonstrated by the successful delivery of a model drug, protoporphyrin IX (PpIX) into T cells [ 6 ]. These findings can be important for the development of dendrimer-based tools for immunotherapy.…”
mentioning
confidence: 99%